Study of Indonesia's National Strategy in Responding to Global and Domestic Challenges - Hastuti Handayani Harahap; Frederick Rudy Sentosa Rajagukguk; Indra Welly Arifin (Journal of Economics, Management, Development, and Education, 2026)
This study aims to examine Indonesia's national strategy in addressing increasingly complex global and domestic challenges, particularly in the areas of the global economic slowdown, commodity price volatility, supply chain disruptions, and climate change. This study uses a qualitative approach with a library research method through analysis of various national policy documents, international agency reports, and the latest scientific publications. The study results indicate that Indonesia's national strategy has been directed at strengthening economic resilience through macroeconomic stability, economic transformation, industrial downstreaming, and strengthening the domestic market. In facing geopolitical challenges and supply chain disruptions, the national strategy encourages diversification of trading partners, strengthening national industry, and improving logistics infrastructure. Meanwhile, in responding to climate change, the national strategy is directed at mitigation and adaptation through energy transition, emission reduction, and strengthening disaster risk management. However, the effectiveness of the national strategy still faces implementation obstacles, such as regional capacity imbalances, limited human resources, weak cross-sectoral coordination, regional fiscal dependency, and suboptimal monitoring and evaluation. This study concludes that Indonesia's national strategy is on the right track, but requires strengthening policy integration, consistency of implementation, and increasing the capacity of central and regional institutions to be more adaptive and effective in facing global pressures and domestic needs in a sustainable manner.